DIGITAL MARKETING STRATEGY TO INCREASE BRAND AWARENESS IN INDUSTRY - Ananta Budhi Danurdara; Dwi Apriyanti Kumalasari; Zeni Zainal Muis (CV. Adiba Aisha Amira, 2025)
A digital marketing strategy is a series of plans to build a business presence in the digital world or the internet through various digital channels. Developing a digital marketing plan aims to raise brand awareness and draw in new clients for the company. A strong digital marketing strategy will help businesses to achieve specific digital goals through properly chosen media. Increasing brand awareness is a worthwhile investment for businesses. By expanding brand knowledge and awareness, businesses can gain a competitive advantage, expand market reach, build customer loyalty, and achieve sustainable growth. The method used in this article is a literature review. This research discusses the description and types of digital marketing, analysis of how digital marketing strategies influence brand awareness, implementation of digital marketing strategies in certain industries, and the effectiveness of digital marketing strategies in increasing brand awareness.